The social function of rationalization: An identity perspective. (15th April 2020) - Van Bavel, Jay J.; Sternisko, Anni; Harris, Elizabeth; Robertson, Claire
Abstract: In this commentary, we offer an additional function of rationalization. Namely, in certain social contexts, the proximal and ultimate function of beliefs and desires is social inclusion. In such contexts, rationalization often facilitates distortion of rather than approximation to truth. Understanding the role of social identity is not only timely and important, but also critical to fully understand the function(s) of rationalization.